POLA ASUH ORANGTUA DALAM PEMBENTUKAN AKHLAK PADA ANAK USIA DINI - Risnawati; Dinda Asri Ramadhani; Sinta Affrilliana Sari; Masganti Sitorus (LPPM IAD Probolinggo, 2024)
This study aims to explore parenting patterns in the formation of early childhood morals. In the context of globalization that brings changes in values, parents are faced with the challenge of educating their children to have good character. This study uses a qualitative method with a phenomenological approach, which allows researchers to obtain in-depth data through interviews and direct observation. The findings demonstrate how parents' parenting styles vary greatly based on the traits of each child and the dynamics of the family. Children's moral development has been demonstrated to benefit from democratic and authoritarian parenting, as seen by improvements in self-esteem, politeness, and goal orientation. This study highlights the value of parents actively teaching their children morality from a young age and the necessity of understanding how technology affects parenting. It is believed that parents would be more equipped to mold their children's moral character in the future if they are aware of the types and advantages of good parenting. Keywords: Parenting, Morals, Early Childhood, Education, Family.